Lived experiences of people living with HIV: a descriptive qualitative analysis of their perceptions of themselves, their social spheres, healthcare professionals and the challenges they face daily - Gamze Senyurek; Mustafa Volkan Kavas; Yesim Isil Ulman (BMC, 2021)
Abstract Background Human immunodeficiency virus (HIV) infection rates have been gradually increasing in Istanbul, Turkey. Many people living with HIV (PLWH) here encounter difficulties, for example, in adapting to the chronic disease and obtaining continuous access to healthcare services. In this study, we aimed to explore the challenges PLWH face in their daily lives and understand their perceptions of themselves, healthcare professionals and services, and their social spheres via their expressed lived experiences in the healthcare setting. Method Individual semi-structured in-depth interviews were conducted face-to-face with 20 PLWH in Istanbul. All the interviews were voice-recorded and transcribed verbatim except one, upon participant request, for which the interviewer took notes. These logs and the interviewer's notes were analyzed thematically using the inductive content analysis method. Results The themes concerned experiences in three distinct contexts: 1) Interactions with healthcare providers; 2) Participants' responses to their HIV diagnosis; and 3) Interactions with their social networks. Firstly, the results highlighted that the participants perceived that healthcare professionals did not inform them about the diagnosis properly, failed to protect patients' confidentiality and exhibited discriminative behaviors towards them. Secondly, after the diagnosis the participants had difficulty in coping with their unsettled emotional state. While many ceased sexual activities and isolated themselves, some sought support. Lastly, living with HIV affected their relationships with their families and friends either positively or negatively. Moreover, they had to face the difficulties concerning spouse/partner notification issues about which many needed professional support. Conclusion Healthcare professionals' discriminative or inappropriate attitudes and customs in healthcare institutions are perceived to impair PLWH's utilization of healthcare services. Structural factors such as social pressure, societal ignorance about HIV, limited access to HIV prevention, and regulatory barriers might contribute to these challenges. The results suggest that it is necessary to raise healthcare professionals' and society's awareness about HIV and develop national policies to establish a well-functioning referral system and appropriate spouse/partner notification services.